Changes in insulin, adiponectin and lipid concentrations with age are associated with frailty and reduced quality of life in dogs - Brennen McKenzie; Matthew Peloquin; Jessica L. Graves; Frances Chen; Ashley Tovar; Tennery A. Carttar; Katya Tucker; Kenny Vo; Michelle Nelson; Kaitlyn M. Super; Jessica Austriaco; Sunny Y. Weber; et al. (Scientific Reports)
Abstract Declining metabolic function with aging is a conserved phenotype across many species. While aging-associated changes in metabolic status have been investigated rigorously in humans, less is known about metabolic aging in dogs. In this cross-sectional study, we aimed to examine changes in metabolic health with age, and any associations with frailty and quality of life, in a diverse population of companion dogs. This cross-sectional study enrolled 451 mature, adult companion dogs. Serum adiponectin, ALP, ALT, AST, cholesterol, insulin, IGF-1 and glucose levels were quantified. Additionally, plasma FFA, SFA, PA, OA and LA were quantified in a 61 dog subpopulation. All analytes were significantly associated with age, with the exception of AST. Elevated ALP, ALT, cholesterol, insulin, FFA, PA and OA were correlated with increased frailty scores, while higher levels of glucose and adiponectin were correlated with reduced frailty scores. The strength of these associations increased with age. Higher ALP, ALT and insulin were associated with lower HRQL scores after adjusting for covariates. Our findings establish novel associations between deleterious aging-associated metabolic changes and validated measures of clinical well-being in companion dogs. Future research should investigate the causality of these associations to inform therapeutic strategies targeting age-associated changes to frailty and quality of life.